2021
DOI: 10.3389/fpsyt.2021.759315
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Interventions Are More Effective in Improving Core Symptoms in Children With ADHD

Abstract: Objective: To investigate the effect of sensory integration training combined with EEG biofeedback on core symptoms in children with ADHD.Methods: Fifty-two children with attention-deficit, hyperactive-impulsive and combined ADHD were selected. They were randomly divided into control group, sensory integration training group, EEG biofeedback group, and sensory integration training + EEG biofeedback group, and after 4 months of intervention, concentration time and impulsive- hyperactivity and hyperactivity inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…It follows that interventions aimed at refining multisensory integration could impact in a bottom-up manner on the development of cognitive and social abilities in neurodevelopmental disorders. 69 , 74 …”
Section: Localizing Multisensory Areas In the Infant Brain Through Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…It follows that interventions aimed at refining multisensory integration could impact in a bottom-up manner on the development of cognitive and social abilities in neurodevelopmental disorders. 69 , 74 …”
Section: Localizing Multisensory Areas In the Infant Brain Through Re...mentioning
confidence: 99%
“… 80 It also has been shown that multisensory-integration-based interventions can significantly decrease autistic mannerisms 81 , 82 , 83 and significantly improve the concentration level of children with ADHD and, in turn, improve the behavioral symptoms of impulsive-hyperactivity and hyperactivity. 74 …”
Section: Localizing Multisensory Areas In the Infant Brain Through Re...mentioning
confidence: 99%